783 Healthy eating choices: employee perceptions of the role of the employer. (24th April 2018) - Grant, Judith; Houdmont, Jonathan; Munir, Fehmidah; Kerr, Robert
Abstract : Introduction: Changes in lifestyles and diet over the last 30 years have led to a significant rise in overweight and obesity. By the year 2020 seven out of ten people in Britain may be overweight or obese, putting a strain on health services and increasing costs to the economy. Organisations may contribute to poor health behaviours, however they are also well placed to support employees; therefore understanding employees' perceptions of the barriers and facilitators to healthy eating at work may assist in designing interventions to address these. Methods: This qualitative study was conducted in 2017 using semi-structured telephone interviews in a large organisation that had recently been privatised after many decades in public ownership. Demographic information collected from participants included three indices of SES (education, income and job type), age, gender, dependents, and perceived weight status. Participants were asked to consider the barriers and facilitators to eating a healthy well-balanced diet and their perceptions of the role of the employer in promoting healthy eating. Thematic analysis was carried out using Braun and Clarke's (2006) methodology and analysis carried out through the computer software NVivo. Result: Thematic saturation was reached upon completion of 15 interviews. Five main themes were identified, each containing multiple sub-themes: Knowledge (fruit and vegetable portions; source of knowledge), Behaviour (cost of food influencing purchasing; eating past the point of feeling full; motivation to eat a healthily), Access (access to healthy foods in the workplace; preparing food in advance), Workplace Culture (long hours and travel; taking breaks; workplace temptation; leadership behaviours) and 5. Responsibility (Government and organisational responsibilities). Discussion: Workplace culture was seen as a barrier to healthy eating. Initiatives designed to modify work culture may prove effective as a means by which to promote healthy eating in the organisational setting.